Aurora A overexpression in breast cancer patients induces taxane resistance and results in worse prognosis - Cirak, Yalcin; Furuncuoglu, Yavuz; Yapicier, Ozlem; Aksu, Asude; Cubukcu, Erdem (Zerbinis Medical Publ, 2015)
Purpose: The aim of this study was to determine the expression level of Aurora A in human breast cancer tissues and to test whether there is a relationship between its expression levels and clinicopathological parameters including response to taxanes, tumor grade, estrogen receptor (ER) status, human epidermal growth factor receptor 2 (HER2) status, and overall survival (OS). Methods: We retrospectively analyzed paraffin-embedded tissue sections from 49 metastatic breast cancer patients whose clinical outcomes had been tracked after taxane treatment. The expression status of Aurora A was defined by immunohistochemistry (IHC) using the anti-Aurora A antibody. Results: Aurora A was overexpressed in 73% of the examined specimens. There was significant correlation between high Aurora A expression and decreased taxane sensitivity (p=0.02). There was no association between the clinicopathological parameters including histologic grade, ER positivity and triple negative molecular subtype and the level of Aurora A expression. However, HER2 positive tumors showed significantly higher Aurora A expression compared with HER2 negative tumors (p=0.02). Kaplan-Meier survival analysis failed to show a significant correlation between expression levels of Aurora A and OS although patients with low Aurora A levels had a marginally longer survival compared to patients with high levels. Conclusion: Our data suggest that Aurora A may be a promising predictive and prognostic marker in patients with breast cancer.
Keywords: Aurora A; breast cancer; HER2; predictive; prognostic; taxanes